Pile design with variation correlation of SPT-N value - Mohd Hafizam Hussin (School of Environmental Engineering, University Malaysia Perlis, 2012)
Since the early of pile static formula suggested by Terzaghi (1943) up until now, several pile design methods is being proposed. This study is conducted based on driven Spun Pile and Reinforced Concrete Pile constructed in Malaysia in sand and cohesive soils. This is to determine the various correlation of undrained shear strength (Cu) and soil friction angle as a measureable factor based on number of SPT - N value., with the End - bearing capacity and Skin Resistance capacity respectively value with static analysis. The Meyerhof method were choose for this case study to estimate and calculate ultimate pile capacity. There are 3 correlation of undrained shear strength (Cu) and 3 correlation of soil friction angle which is act as the main content for this research. Only one type of pile one size of is use in this study to limit the research which is more focus on various correlation of soil parameter. For undrained shear strength (Cu) this study use a derivation from British Standard table (BS 5930), (Cu = 6N) and a derivation from (Hara et al. 1971). It is also used soil friction angle which is obtained from table (Bowels, 1997), table (Meyerhof, 1976) and equation from (Shioi and Fukui, 1982). All the calculation on pile design is being done in excel spreadsheet. From this study, it can be conclude that to use a parameter of undrained shear strength (Cu) introduced from (Hara et al. 1971) and use parameter of soil friction angle derived from (Shioi and Fukui 1982).